Pozabljeni Kamnik in njegovo jezeroForgotten Kamnik and Its Lake - Klobčar, Marija (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">During ethnological-folkloristic work in the Kamnik area, I often came across accounts of Kamnik or Nevlje Lake in the narratives of the local people. At the same time, encountered clearly expressed doubts regarding this tradition. This led to the explanation of the existence of the lake as early as when Christianity had spread across Slovenia. This explanation indicates new understanding of the town itself: it points to the existence of unknown Kamnik.